Effect of Carallia brachiata Ethanolic Extract on Adipogenesis in 3T3-L1 Adipocytes - Chularojmontri, Linda; Nanna, Urarat (Asian Medical Journal and Alternative Medicine, 2022)
Introduction: An excessstorage of body fat causes obesity. Since obesity increasesrisk of chronic diseases, thusit isimportant to inhibit excessive storage of fat. Carallia brachiata is a plant that found in Thailand. There is a report that the leaf of Carallia brachiata has an antidiabetic effect in rat model. Objectives: The aim of this study was to demonstrate the effect of Carallia brachiata leaf and stem ethanolic extracts (CL and CS) on adipogenesis in 3T3-L1 adipocytes. Methods: 3T3-L1 adipocytes were used for measuring cytotoxicity of CL and CS (3, 10, 30, and 100 μg/mL). To determine adipogenesis process, CL and CS extracts were added to the cell culture medium at concentrations of 0, 3, 10, 30 and 100 μg/mL. After 8 days of treatments, adipocyte cells were stained with Oil Red O solution and measured the expression of adipogenic genes. Results: CL and CS did not inhibit cell proliferation and showed no cytotoxicity in 3T3-L1 cells. Therefore, concentration range of 3 - 100 μg/mL CL and CS was used for subsequent experiments. CS inhibited lipid accumulation in 3T3-L1 adipocytes and suppressed gene expression of CCAAT/enhancer-binding protein α (C/EBPα), peroxisome proliferator-activated receptor γ (PPARγ), sterol regulatory element binding protein 1c (SREBP1c), adipocyte-specific genes fatty acid synthase (FAS), lipoprotein lipase (LPL) and adipocyte fatty acid-binding protein 2 (aP2). Whereas, CL dis not inhibit lipid storage and only had an inhibitory activity on SREBP1c and aP2 genes. Conclusions: Our findings suggest that Carallia brachiata has an inhibitory effect on adipogenesis could be partially caused by suppressing C/EBPα, PPARγ and SREBP1c genes in 3T3-L1 adipocytes